Policy Adoption and the Implementation Woes of the Intersectoral First 1000 Days of Childhood Initiative, In the Western Cape Province of South Africa - Ida Okeyo; Uta Lehmann; Helen Schneider (Kerman University of Medical Sciences, 2021)
BackgroundThere is a growing interest in implementing intersectoral approaches to address social determinants especially within the Sustainable Development Goals (SDGs) era. However, there is limited research that uses policy analysis approaches to understand the barriers to adoption and implementation of intersectoral approaches. In this paper we apply a policy analysis lens in examining implementation of the first thousand days (FTD) of childhood initiative in the Western Cape province of South Africa. This initiative aims to improve child outcomes through a holistic intersectoral approach, referred to as nurturing care. MethodsThe case of the FTD initiative was constructed through a triangulated analysis of document reviews (34), in depth interviews (22) and observations. The analysis drew on Hall's 'ideas, interests and institutions' framework to understand the shift from political agendas to the implementation of the FTD. ResultsIn the Western Cape province, the FTD agenda setting process was catalysed by the increasing global evidence on the life-long impacts of brain development during the early childhood years. This created a window of opportunity for active lobbying by policy entrepreneurs and a favourable provincial context for a holistic focus on children. However, during implementation, the intersectoral goal of the FTD got lost, with limited bureaucratic support from service-delivery actors and minimal cross-sector involvement. Challenges facing the health sector, such as overburdened facilities, competing policies and the limited consideration of implementation realities (such as health providers' capacity), were perceived by implementing actors as the key constraints to intersectoral action. As a result, FTD actors, whose decision-making power largely resided in health services, reformulated FTD as a traditional maternal-child health mandate. Ambiguity and contestation between key actors regarding FTD interventions contributed to this narrowing of focus. ConclusionThis study highlights conditions that should be considered for the effective implementation of intersectoral action - including engaging cross-sector players in agenda setting processes and creating spaces that allow the consideration of actors' interests especially those at service-delivery level. Networks that prioritise relationship building and trust can be valuable in allowing the emergence of common goals that further embrace collective interests.